Alcohol state markers- facility and utility for clinical management of alcohol use disorders: study from a tertiary care centre in South India - J., Liji M.; Varghese, P. R.; Innah, Susheela Jacob; Kuttichira, Praveenlal (International Journal of Research in Medical Sciences, 2021)
Background: Alcoholism is broadly any drinking of alcohol resulting in significant psychological and physiological health problems. As alcoholism is not a recognized diagnostic entity the detection and monitoring of the clinical manifestations of alcoholism is of great importance in the alcohol use disorders (AUD) treatment. Hence, the use of alcohol biomarkers plays a vital role in the diagnosis, treatment and prognosis of AUDs. Methods: This study aimed to understand the utility of state markers in alcohol related distress, both for diagnosis and prognosis in a tertiary care centre. The relative number and the frequency of the alcohol biomarker tests such as AST (aspartate aminotransferase), ALT (alanine aminotransferase), MCV (mean corpuscular volume) and GGT (gamma-glutamyl transferase) investigated in the hospital departments (32 departments) were collected. Test requests and results in January to March on five consecutive years from 2016 to 2020 were analyzed, by comparing psychiatry department with all other departments and AUD with non-AUD cases. Results: The study findings revealed that, the tests AST, ALT and MCV were well utilized for the AUD treatment procedure in the tertiary care centre, irrespective of the department the patient got admitted. Since GGT was the least preferred test, the figures of GGT could not be analysed because of the exceptionally low number. Conclusions: The utility of the commonly available alcohol biomarker tests is especially useful for the clinical management of AUD patients and these are well utilized in an appreciable manner in the study centre. Development of more accurate, specific, and sensitive panel of biomarker tests may further motivate clinicians to better monitor individuals who suffer from alcoholism.